2013
DOI: 10.1016/j.polymertesting.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Carrier gas flow arrangement based photoacoustic detection method for measuring gas permeability of polymer membranes

Abstract: This paper describes a membrane permeability measuring setup based on photoacoustic spectroscopy using continuous carrier gas flow to transport the permeated analyte molecules into a photoacoustic detection cell. The permeability parameters of the sample were determined from the measured permeation curves by using a numerical curve fitting algorithm. The method was applied to different membrane samples for determining methane and carbon-dioxide permeability at various carrier gas flow rates (CFRs). For each sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The experimental curves are the results of our earlier works where the concentration of the molecules permeating through the membrane was measured by using the laser based photoacoustic detection system in a carrier gas flow arrangement [3]. Fluxes through the membrane are calculated by multiplying the measured concentrations with the carrier gas flow rate and by dividing the results with the area of the measured membrane sample.…”
Section: Measured Permeation Curvesmentioning
confidence: 99%
“…The experimental curves are the results of our earlier works where the concentration of the molecules permeating through the membrane was measured by using the laser based photoacoustic detection system in a carrier gas flow arrangement [3]. Fluxes through the membrane are calculated by multiplying the measured concentrations with the carrier gas flow rate and by dividing the results with the area of the measured membrane sample.…”
Section: Measured Permeation Curvesmentioning
confidence: 99%
“…In recent years the number of reported photoacoustic (PA) instruments to prove their applicability in various areas has been steadily increasing [1][2][3][4]. Amongst these instruments are those which were developed by our research group for various applications, including in the natural gas industry [5][6][7], airborne hygrometry [8][9], source apportionment of urban light-absorbing aerosols [10][11], measurements of gas permeability [12], and clinical research [13]. The main components of our instruments are basically always the same: a data acquisition and control system (DACS), one or more longitudinal differential detection cells [14], (a) modulated light source(s) which is/are either telecommunication-type diode lasers [15] or frequency converted Nd:YAG lasers [10] and gas handling units in various configurations.…”
Section: Motivationmentioning
confidence: 99%
“…In most cases, the DACS has various additional functions such as controlling the gas handling system and communicating with other instruments. Our recently developed systems [5][6][7][8][9][10][11][12][13] were based on a highly integrated target DACS. This system turned out to be one of the bottlenecks during the application developments due to its limited capabilities; therefore, a fundamental redesign of our DACS became essential.…”
Section: Motivationmentioning
confidence: 99%
“…In order to differentiate the permeated molecules from the molecules of the carrier gas the applied detection method has to be selective. Among the possible methods Beer-Lambert law based optical absorption measurement techniques are fairly popular [ 2 ], as well as photoacoustic (PA) detection, which is a special type of optical absorption method that already has been applied successfully in permeation measurements [ [3] , [4] , [5] ]. Previous research has shown that a properly optimised PA system outperforms conventional optical absorption detection techniques as far as the minimum detectable concentration and the response time is concerned [ 6 ].…”
Section: Introductionmentioning
confidence: 99%